Nanocrystals (IntechOpen, 2023)
Nanocrystals research has been an area of significant interest lately, due to the wide variety of potential applications in semiconductor, optical and biomedical fields. This book consists of a collection of research work on nanocrystals processing and characterization of their structural, optical, electronic, magnetic and mechanical properties. Various methods for nanocrystals synthesis are discussed in the book. Size-dependent properties such as quantum confinement, superparamagnetism have been observed in semiconductor and magnetic nanoparticles. Nanocrystals incorporated into different material systems have proven to possess improved properties. A review of the exciting outcomes nanoparticles study has provided indicates further accomplishments in the near future.